1997
DOI: 10.1007/s002449900173
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Association of Trace Metals in Soft Tissue and Byssus of Mytilus edulis from the East Coast of Kyushu Island, Japan

Abstract: Concentrations of Cd, Pb, Zn, Cu, Ag, Cr, Co Ni, Mn, andFe in soft tissues and byssi of blue mussel (Mytilus edulis) fromthree sites along the east coast of Kyushu Island, Japan, were determined byAAS method. Large inter-regional differences in metal concentrations in bothsoft tissues and byssi (Cu, Cd, and Pb and Cu, Pb, Co, Ni, Mn, and Fe,respectively) were recorded. Highly significant correlations (p< 0.01) were observed between tissue and byssal concentrations of Pb,Cu, Zn, and Mn. The tissue concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Ikuta [23] found that when high levels of heavy metals were accumulated in the ST of the mussel M. edulis, these heavy metals would almost proportionally be transferred to the byssus. The byssus of M. edulis was shown to be a good biomonitoring tool for Cu [24] and Hg [6]. In this study, we have found that the byssus of P. viridis is a good biomonitoring instrument for Zn.…”
Section: Discussionmentioning
confidence: 84%
“…Ikuta [23] found that when high levels of heavy metals were accumulated in the ST of the mussel M. edulis, these heavy metals would almost proportionally be transferred to the byssus. The byssus of M. edulis was shown to be a good biomonitoring tool for Cu [24] and Hg [6]. In this study, we have found that the byssus of P. viridis is a good biomonitoring instrument for Zn.…”
Section: Discussionmentioning
confidence: 84%
“…Mytilus spp. have been considered to be potential biomonitors of toxic metals in marine ecosystems (Fowler and Oregioni, 1976;Koide et al, 1982;Szefer et al, 1997Szefer et al, , 1999aChase et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Mussels are known to accumulate metal ions in their byssal threads at a concentration significantly higher than that of the surrounding sea water [44,45]. Accumulation of these ions at such a high level is due to the presence of DOPA in the byssus [46].…”
Section: Reversible Physical Interactionsmentioning
confidence: 99%